180. Best Practice Advisory Decreases Inpatient Urine Culture Orders. (26th November 2018) - Skinner, Alisha; Young, Heather; Shihadeh, Kati; Knepper, Bryan; Jenkins, Timothy C
Abstract: Background: Overprescribing of antibiotics for asymptomatic bacteriuria is common and studies reveal that antibiotic prescriptions often correlate with a positive urinalysis (UA) or urine culture (UCx), rather than signs or symptoms of a urinary tract infection. In attempts to decrease inappropriate UCx orders, the antimicrobial stewardship team developed a best practice advisory (BPA) within our electronic health record (EHR). The objective of this study was to evaluate the effects of the BPA on the number of UCx performed. Methods: This intervention took place in an urban, level 1 trauma, public safety, teaching hospital. A BPA was developed within the EHR (Epic), which activated if a standalone UCx was ordered on a patient without a positive UA within the past 24 hours (defined as ≥10 WBC/HPF) (Figure 1). The BPA prompted providers to discontinue the UCx order and alternatively order a UA with reflex to culture (excluding pregnant women, immunocompromised, children <3 years old, urine collected by straight catheterization, or patients undergoing urologic procedures). In this retrospective pre-intervention–postintervention study, the preintervention period was May 2016 through October 2017, and the intervention period was December 2017 through March 2018. The BPA was activated in November 2017. The primary outcome was UCx performed/1, 000 patient-days. Results: During the 4-month intervention period, the BPA was activated 120 times. The UCx order was replaced by a UA with reflex to culture in 47% (56/120) of cases, while removal of the UCx alone was seen in 6% (7/120) of cases. The remainder of cases did not remove the original order with reasons including urine sample obtained by straight catheterization, urine culture added to prior urinalysis, a critically ill patient with encephalopathy (Figure 2). During the intervention period, there was a statistically significant decrease in both the number of standalone UCx performed from 41.2/1, 000 patient-days to 30.1/1, 000 patient-days ( P = 0.008) and the total number of UCx performed 58.7/1, 000 patient-days to 53.0/1, 000 patient-days ( P = 0.02) (Figure 3). Conclusion: Implementation of a BPA to prevent the use of standalone UCx in favor of a UA with reflex culture reduced the total number of UCx performed. Disclosures: All authors: No reported disclosures.